Applications of α, β-Symmetrical Functions on a Certain Class of Spirallike Functions. (30th June 2022) - Alkhammash, Aljazi; Alsarari, Fuad
Abstract : In this note, we use the notions of α, β -symmetrical, generalized Janowski-type and spirallike functions to define a new class S α, β λ N, M, μ defined in the open unit disk. In particular, we obtain a structural formula, a representation theorem, Marx-Strohacker inequality. Our results continue to hold the covering and distortion properties.